Wiedza glottodydaktyczna w służbie logopedii międzykulturowej - Biernacka, Michalina (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The developing intercultural speech therapy is supported by Polish language glottodidactics. It is worth considering the experience of many years of teaching Polish as a foreign/second/inherited language as well as the language of school education in the process of diagnosis and therapy. The aim of this paper is to answer the question: how glottodidactic knowledge can be useful in the daily work of a speech therapist? It will be discussed how the developed teaching methods and techniques may be useful in the context of the speech therapist’s work.